Characteristics of Families with Family Duties in the Prevention of Premarital Sexual Behavior in Adolescent Children in the Working Area of Sunyaragi Health Center Cirebon - Nurhaeni, Ani; Erna Marisa, Dewi; Oktiany, Thia; Susan, Yanti (Ann Publisher, 2024)
Disseminating societal standards and values begins with the family, considered the most significant institution for an individual. The family serves as a mold for a child's conduct and mindset, particularly during their teenage years. Finding out how family chores and features relate to preventing premarital sex behavior among teenage children working in the village health center of Cirebon City was the aim of this study. The study design used in this study is cross-sectional and descriptive correlational. Thirty-two individuals were sampled using the random sampling technique. A survey is the tool that is employed. Chi-square analysis of data. June 2021: Study location at Puskesmas Sunyaragi Cirebon City Work Area. The study's findings indicate that the majority of married families—sixteen (18.8%)—are separated or divorced; separated or not, three houses—nineteen (9.4%)—interact and communicate negatively; and families with as many as twenty-six (81.3%) have a single culture. H0 was rejected, as indicated by the p-value <α derived from the chi-square test findings. In the Sunyaragi Health Clinic in Cirebon City, there is a correlation between homeownership, family responsibilities, and marital status when it comes to preventing premarital sex activity in teenage children. The P-value is 0.002, α is 0.05. Advice from parents or other family members to shield adolescents from harmful influences and steer clear of undesirable sexual behavior.